Enzyme inspired polymer functionalized with an artificial catalytic triad. (26th May 2021) - Bhaskaran, Ayana; Aitken, Heather M.; Xiao, Zeyun; Blyth, Mitchell; Nothling, Mitchell D.; Kamdar, Shashank; O'Mara, Megan L.; Connal, Luke A.
Abstract: At the heart of an enzyme's structure is the active catalytic site, which, together with the surrounding amino-acid residues, tunes the substrate properties in the electrostatic microenvironment. Taking inspiration from nature's catalytic triad, consisting of a hydroxyl group of a serine residue, an imidazole group of a histidine residue, and a carboxyl group of an aspartic acid, a polymer scaffolded enzyme mimic is incorporated with artificial catalytic triad units. It is demonstrated that controlling the local environment of the artificial triad affects catalytic activity. Compared to a water soluble artificial catalytic triad, enhanced esterolytic activity of p-nitrophenyl benzoate was observed for the polymeric catalyst possibly due to the hydrophobic microenvironment formed by the tertiary structure of the polymer backbone. The different environments were supported by molecular dynamics simulations. It is further demonstrated that the cross-linked catalytic triad functional polystyrene could be used as a reusable solid support catalyst for esterolysis. Graphical abstract: Enzymes accelerate chemical reactions with remarkable catalytic efficiency. At the heart of the protein structure is the active catalytic site, which, together with the surrounding amino-acid residues, tunes the substrate properties in the electrostatic microenvironment. Taking inspiration form the nature's catalytic triad in hydrolytic enzymes, consisting of a hydroxyl group of a serine residue, an imidazole group of a histidine residue, and a carboxyl group of an aspartic acid in the three-dimensional space, here we report a polymer scaffolded enzyme mimic incorporated with artificial catalytic triad units. We demonstrate that by controlling the local environment of the artificial triad the catalytic activity is affected. Compared with a water soluble artificial catalytic triad, an enhanced esterolytic activity on p-nitrophenyl benzoate was observed for the polymer-based artificial trial possibly due to the hydrophobic microenvironment formed by the tertiary structure of the polymer backbone – similar to native enzyme hydrophobic pockets. The different environments were supported by molecular dynamics simulations. We also demonstrate that the crosslinked catalytic triad functional polystyrene could be used as a reusable solid support catalyst for esterolysis. Image 1 Highlights: Polymer supported enzyme mimic. Recyclable bioinspired catalyst. Molecular dynamics highlights the importance of hydrophobicity.